Impact of ultrasound pretreatment on hydrolysate and digestion products of grape seed protein - Ding, Qingzhi; Zhang, Ting; Niu, Shuai; Cao, Feifan; Wu-Chen, Ricardo Antonio; Luo, Lin; Ma, Haile (Ultrasonics sonochemistry, 2018)
•Frequency effects of ECFU pretreatment on enzymolysis of GSP were studied.•IC50 of the digestion products were investigated.•Structural characteristics of the GSP by ECFU pretreatment were further studied. The effects of ultrasound pretreatment with different working modes, including mono frequency ultrasound (MFU), simultaneous dual frequency ultrasound (SDFU) and alternate dual frequency ultrasound (ADFU) using energy-gather counter flow ultrasound equipment, on the degree of hydrolysis (DH) of grape seed protein (GSP) hydrolysate and IC50 of GSP digestion products were studied. Amino acid composition analysis (AACA), ultraviolet–visible (UV) spectroscopy and atomic force microscopy (AFM) of GSP with different ultrasound pretreatments were measured. The results showed that MFU, SDFU and ADFU pretreatments improved the DH and reduced the IC50 of GSP significantly (P < .05). The MFU of 20 kHz and SDFU of 20/40 kHz showed higher ACE inhibitory activity within the MFU and SDFU groups, respectively. ADFU of 20/35 kHz produced the highest ACE inhibitory activity among the three working modes (MFU, SDFU and ADFU). AACA showed that all the working modes of the ultrasound pretreatment could increase the amount of hydrophobic amino acids and the total amino acids. The changes in UV spectra and amino acid analysis indicated the unfolding of protein structure and exposure of more hydrophobic groups by SDFU and ADFU pretreatments. AFM analysis of the GSP indicated that the microstructures were destroyed and the particle size reduced after dual-frequency ultrasound pretreatments. Therefore, energy-gather counter flow ultrasound pretreatment is an effective method to improve the DH and reducing the IC50 due to the changes of molecular conformation and effects on the microstructure by sonochemistry of GSP. In conclusion, it is necessary to select the frequency and working modes of ultrasound pretreatment for the preparation of ACE inhibitory peptide of GSP.